BOTANICAL NOTES ON THE IDENTITY OF CERTAIN HERBS USED IN AYURVEDIC MEDICINES IN KERALA .II - V.V.SIVARAJAN and INDU BALACHANDRAN (Ancient Science of Life, 1985)
In the first part the authors have discussed the botanical identity of the drug ‘Thamalaki’ as it is used in Kerala. The second part deals with the identity of a few more drugs namely, ‘Puskaramula, Punarnava, Suryavartha and Nirgundi